Chemical communication in crustaceans - Breithaupt, Thomas; Thiel, Martin; SpringerLink (Online service). (New York Springer, 2011)
Crustaceans are ecologically and economically important. They are fished and farmed extensively for food and are model organisms for scientific research. However, as invasive species, some crustaceans also threaten native communities world-wide. Social interactions of these primarily aquatic invertebrates are generally mediated through chemicals. Hence, the study of chemical communication by crustaceans is fundamental to understanding their biology and developing strategies to manage and protect them. Research in this area also promises discoveries of new waterborne natural products. This book provides the first comprehensive synthesis of current knowledge on crustacean chemical communication. Leading experts review different aspects of chemical communication and share their fascination with their research with the reader. Opening with an overview of the challenges and concepts of crustacean chemical communication research, the book proceeds to explore signal transmission and reception, and neural processing. The behavioral context of chemical communication is reviewed for the best-studied species. Recent advances in the molecular identification of crustacean chemical signals are presented, followed by discussions of their possible applications in aquaculture and management. Additional chapters provide complementary knowledge from other taxa (fish, insects) and topics (multimodal communication, deception, ecotoxicology), highlighting opportunities for future research. The book is richly illustrated and avoids technical jargon, making it accessible to a broad readership including researchers and students of ecology, evolution, behavior, and neurobiology, as well as non-scientists interested in fisheries, aquaculture, and environmental management. ?This excellent and comprehensive volume fills a major gap in the field of chemical ecology and behavioral physiology. The editors assembled an outstanding group of expert contributors.? - Bert Hölldobler, Arizona State University and University of Würzburg ?The topics are timely, the reviews current and the approach refreshingly synthetic. I see this book being useful for many years to come to the entire community of aquatic chemical ecologists.? - Peter W. Sorensen, University of Minnesota ?The chapters are lucidly written by the outstanding experts in their fields. The book is a must-read for all those interested in the underwater world.? - Jelle Atema, Boston University and Woods Hole Oceanographic Institution ABOUT THE EDITORS Thomas Breithaupt is a lecturer in the Department of Biological Sciences at the University of Hull (UK) where he studies the mechanisms and evolution of chemical communication and orientation in crustaceans and fish. Martin Thiel is professor of Marine Biology at Universidad Católica del Norte in Coquimbo (Chile) where together with his students he uses crustaceans as model organisms to study the evolution of social behavior in the sea.
Part I. Introductory Section: General Introduction. Pheromones and behaviour - overview, definitions -- Part II. General Overview of Signal Characteristics and Reception: Finding the mate: Pheromone hydrodynamics and odour acquisition. Orientation to pheromone sources in turbulent plumes. Functional morphology of chemoreceptors. Olfaction and pheromone reception in crustaceans. Processing of chemical information in the crustacean brain. Beyond crustaceans: The nature of communication chemicals: their solubility and volatility, stability and specificity. Pheromone communication in aquatic and aerial environments -- Part III. Chemical Communication and Behaviour: Chemical communication in lobsters. Chemical communication in crayfish. Chemical modulation of aggressive interactions in stomatopods. Alarm substance and predator avoidance in crustaceans. Chemical communication in shrimp. Chemical communication in peracarid crustaceans. Chemical communication in anomurans. Chemical communication in terrestrial crustaceans. Chemical communication in copepods. Beyond crustaceans: Honest signals or deceit ? how reliable are pheromones? Chemical communication in a multi-modal context -- Part IV. Towards Identification of Chemical Signals: Identification of a sex pheromone in decapod crustaceans. Chemical communication and hormones. Settlement cues of barnacles. Beyond crustaceans: A review of pheromone communication in fish -- Part V. Applied Aspects: The use of pheromones in integrated pest managements (IPM). Environmental contamination and effects on chemical communication. Principles of crustacean farming: Problems and solutions.
Electronic reproduction.
Keywords: Crustacea -- Behavior; Crustacea -- Physiology; Chemical senses; Animal communication; Crustacea -- Chemical defenses; Crustacea -- Effect of chemicals on; Semiochemicals; Pheromones -- Receptors; Electronic books